Design of GaN‐based surface plasmon LEDs to enhance the modulation bandwidth and light output. Issue 5 (22nd December 2015) - Liu, Lei; Zhao, Lixia; Zhu, Shichao; Yu, Zhiguo; An, Pingbo; Yang, Chao; Wu, Chunhui; Li, Jinmin
Abstract: Gallium nitride based light emitting diodes have shown their advantages in the application of visible light communication (VLC) besides general illumination. However, the modulation bandwidth of current commercial GaN based LEDs still cannot meet daily application of VLC. It has been reported that the modulation bandwidth can be enhanced by the surface plasmon due to the coupling between the surface plasmon and the active region of LEDs. However, the light output may be decreased. In this study, we designed a GaN‐based surface plasmon LEDs using lateral coupling to both increase the light output and the modulation bandwidth. The finite difference time domain method was utilized to investigate the modulation bandwidth of the GaN‐based surface plasmon LEDs as well as the light output. Simulation results show that the modulation bandwidth was estimated to be ∼2.3 GHz with 2.5 times enhancement of the light output compared with conventional LED structure. This design of surface plasmon LEDs will be useful for applications in high frequency visible light communication. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)